Phytochemical Screening of Wellawel (Chromolaena odorata) leaves, its Antimicrobial and Coagulative Properties - Reotutar, Larguita P.; Supnet, Gemma Agnes R. (JPAIR Multidisciplinary Research, 2008)
The study was conducted to perform phytochemical screening, antimicrobial assay and determine the coagulating effects of wellawel (Chromolaena odorata) leaves. This study made use of the experimental research design in an actual laboratory set-up.  There were four phases in the experimental study.  Phase 1 included the preparation of the plant sample and extraction using distilled water and ethyl alcohol, Phase 2 is the phytochemical screening to determine he presence of alkaloids, quaternary bases or amine oxides, saponins, free fatty acids, cardiac glycosides, leucoanthocyanins, flavonoids, tannins, fats and oils and anthraquinones in the leaf extract, Phase 3 is the antimicrobial assay to determine the zones of growth inhibition produced by the wellawel leaf extract to test organisms and Phase 4 is the determination of the coagulating effects of the wellawel leaf against Swiss mice. Findings showed that wellawel  (Chromolaena odorata) leaf  extract contains alkaloids, cardiac glycosides, luecoanthocyanins, flavonoids and tannins. Wellawel leaf extract has weak antimicrobial activity against Bacillus subtilis, Escherichia coli and no anti-fungal activity on Candida albicans. The crude and aqueous extracts have the ability to shorten the coagulation time of blood on wounds inflicted on Swiss mice. Based on the findings, the following recommendations were drawn: a follow up study should be conducted to quantify, isolate and identify the type of alkaloids, cardiac glycosides, leucoanthocyanins, flavonoids and tannins present in the leaves of wellawel and other pharmacologic testing should be done using the wellawel leaves like tests for its analgesic  property, antispasmodic, antihypertensive and antihelminthic properties.
Keywords: Chromolaena odorata; wellawel leaves; phytochemical screening; antimicrobial assay; coagulating effects; alkaloids; flavonoids; tannins; cardiac glycosides; leucoanthocyanins; distilled water extraction; ethyl alcohol extraction; Bacillus subtilis; Escherichia coli; Candida albicans; Swiss mice; pharmacological properties; experimental research design